2011
DOI: 10.2147/copd.s15968
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for unrecognized obstructive lung disease among urban drug users

Abstract: BackgroundObstructive lung disease (OLD) is frequently unrecognized and undertreated. Urban drug users are at higher risk for OLD due to race, behavioral, and socioeconomic characteristics, yet little data exist on prevalence and risk factors associated with unrecognized OLD in this population.ObjectiveThe objective of this study is to determine the prevalence of unrecognized OLD in an urban population and identify the characteristics associated with lack of physician-diagnosed OLD.DesignCross-sectional analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
2
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 44 publications
2
31
2
1
Order By: Relevance
“…For this analysis, all HIV-infected Lung-HIV participants from the United States sites who contributed clinical and demographic data, spirometric measures, and HIV-related laboratory testing were included (see Supplemental Digital Content 1 for contributing centers and participant selection). While individual sites have previously included data on lung function in subsets of participants included in this analytical cohort,[10, 21, 2427] prior analyses included spirometry measurements obtained at different time points during follow-up or in the context of different research objectives. Prior publications have not published on restrictive physiology patterns or compared risk factors for obstruction and restriction versus normal spirometry pattern among HIV-infected individuals.…”
Section: Methodsmentioning
confidence: 99%
“…For this analysis, all HIV-infected Lung-HIV participants from the United States sites who contributed clinical and demographic data, spirometric measures, and HIV-related laboratory testing were included (see Supplemental Digital Content 1 for contributing centers and participant selection). While individual sites have previously included data on lung function in subsets of participants included in this analytical cohort,[10, 21, 2427] prior analyses included spirometry measurements obtained at different time points during follow-up or in the context of different research objectives. Prior publications have not published on restrictive physiology patterns or compared risk factors for obstruction and restriction versus normal spirometry pattern among HIV-infected individuals.…”
Section: Methodsmentioning
confidence: 99%
“…Chronic obstructive pulmonary disease (COPD) is one of the most common non-infectious pulmonary complications observed among HIV+ patients, 1517 and occurs more frequently in this patient population than among uninfected individuals. 4,18 While COPD is strongly associated with increased CAP risk in uninfected patients, 1923 no studies have focused on the role of COPD in the risk for CAP and other pulmonary infections amongst HIV+ patients.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, 50% of this cohort with spirometrically confirmed airflow obstruction had never received a physician diagnosis of obstructive lung disease; current ART use was independently associated with greater prevalence of unrecognised obstructive lung disease. 38 A combined analysis of data from two large observational cohorts of HIV-infected men and women obtained before and after widespread ART use provided insight into the potential role of ART in mitigating longitudinal COPD risk. 37 Compared with HIV-uninfected men in the Multicentre AIDS Cohort Study, HIV-infected men had a nearly three times greater risk of self-reported COPD diagnosis in the era before ART (hazard ratio [HR] 2·9, 95% CI 1·02–8·4).…”
Section: Hiv-associated Obstructive Lung Diseases After the Introductmentioning
confidence: 99%